INDUCTION OF RHAMNOLIPID PRODUCTION BY PSEUDOMONAS AERUGINOSA A3 USING CHEMICAL AND PHYSICAL MUTAGENIC FACTORS - & et al., Faqri (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was depend to select Pseudomonas aeruginosa A3 as a good producer of rhamnolipid (RL) biosurfactant after screening on agar plate where it was able to biosynthesize 4.3 g/L with emulsification index 52% and reducing the surface tension of water to 33.2 mN/m. Therefore, this study was aimed to increase the production of biosurfactant from selected isolate by exposure to several physical and chemical mutagenic factors like gamma radiation, nitrosoguanidine, ethyl methane sulfonate and lithium chloride. The results were shown that 0.2 g/L of nitrosoguanidine was the best mutant for increasing the production to about 2 folds (9.4 g/L) after 15 mins exposure to this material, as well as the emulsification index and surface tension of water were reached to 62% and 26.1 mN/m, respectively, comparing with non-mutant isolate. Also, the critical micelle concentration (CMC) and critical micelle dilution (CMD) of produced rhamnolipid were reached to 120 mg/L and 100 fold, respectively. The optimum conditions of RL production from mutant isolate were determined as 34ºC a best temperature, 6.5 optimum pH and incubation period of 108 h where the production was reached to 10.6 g/L and emulsification index 64% with surface tension of water 26 mN/m. characterization study of purified RL by using thin layer chromatography (TLC) analysis indicated that it was composed of a mixture of mono and di-rhamnolipid.